O estresse e a função gerencial: estudo em uma empresa do segmento de Contact Center na cidade de Belo Horizonte - Fernanda Cristina Costa Couto (2010)
Taking into account that one of the biggest challenges that managers in the segment of contact center is to be agile facing the pressures that are suffering, this paper aims to identify in a company of the contact center segment specific aspects of the manager's job in middlemanagementpositions and operational management, causing excessive tension, analyzing the intensity and the possible manifestations of stress tables, taking into account the gender. To achieve this goal, there was a case study characterized as descriptive and explanatory, which analyzed a sample of 120 managers in one organization at a call center. The data collection was done through the questionnaire that adheres the Theoretical Model Explanation of Occupational Stress on Managers (MTEG) developed by Zille (2005) and the data were treated statisticallyfrom the use of Excel software and SPSS - Statistical Package for Social Sciences. The results showed that 26.7%, or 32 managers, shows absence of stress, but nevertheless, 73.4%, or 88 managers, present manifestation of stress, stress ranging from mild to moderate to very intense stress. Of these, 28.4%, or 34 managers, present a profile of extreme stress and very intense. Also noteworthy is that in terms of seniority, it was noticed that the mid-level managers have higherlevels of stress than managers at the operational level. Of those, 93.3% were under stress, compared with 70.5% of operating managers who presented the same picture. It should be noted that the main sources of tension existing over the work environment were identified byperforming multiple activities at once, with a high degree of pressure for results, the many times and tight deadlines and work routine, causing great discomfort and excessive tension and the perception that the philosophy of top management / board is guided by obsession and compulsion for results, causing excessive stress. The main symptoms of stress are anxiety, fatigue, anxiety, headache tension, and lack or excess of appetite. The manifestations of stress in relation to gendershowed that female managers are presented with a higher incidence of stress than male managers and with respect to the main effects of stress on productivity of managers was the desire to change jobs with frequency often the difficulty remembering recent events related to the work that previously were easily remembered and even the impact of losing control over life events (work, etc.).